STRUCTURAL-PARAMETRIC SYNTHESIS OF ROLLING MILLS MULTI-MOTOR ELECTRIC DRIVES - B. I. Kuznetsov (National Technical University "Kharkiv Polytechnic Institute", 2020)
Aim. Improving of control accuracy by rolling strip thickness and tension and reducing of sensitivity to changes of plant parameters based on structural-parametric synthesis of robust control by rolling mills multi-motor electric drives with parametric uncertainty. Methodology. The method of structural-parametric synthesis of robust control by rolling mills multi-motor electric drives with parametric uncertainty which improves control accuracy by rolling strip thickness and tension and reducing of sensitivity to changes of plant parameters is developed. The method based on the multi-criteria game decision in which payoff vectors are dispersions of longitudinal thickness and tension of the rolled. The calculation of the payoff vector associated with modeling of the synthesized system with different input signals and for various values of the plant parameters for various modes of operation of the system. The multi criterion game solution is calculated based on particles multiswarm optimization algorithms. Results. The results of the structural-parametric synthesis of robust control by 740 three-stand cold rolling mills multi-motor electric drives are presented. Comparisons of the strip thickness and tension accuracy of the synthesized robust system with the existing system are completed. It is showed that the use of synthesized robust controllers allowed to improve strip thickness and tension accuracy and reduce the sensitivity of the system to changes of plant parameters in comparison with the existing system. Originality. For the first time the method of structural-parametric synthesis of robust control by rolling mills multi-motor electric drives with parametric uncertainty based on multi-criteria game decision and particles multiswarm optimization algorithms to improve the control accuracy by rolling strip thickness and tension and to reduce of sensitivity to changes of plant parameters is developed. Practical value. Practical recommendations on reasonable choice of the structure and parameters of robust control by 740 three-stand cold rolling mills multi-motor electric drives to improving of control accuracy by rolling strip thickness and tension and reducing of sensitivity to changes of plant parameters are given.